2017
DOI: 10.5194/nhess-17-595-2017
|View full text |Cite
|
Sign up to set email alerts
|

Disaster risk reduction education in Indonesia: challenges and recommendations for scaling up

Abstract: Abstract. This article investigates the implementation of disaster risk reduction education for children in Indonesia. In the last decade, education programmes related to this subject have been promoted as capable of reducing disaster losses and increasing resilience, based on several studies that have identified positive outcomes. Therefore, it is critical to evaluate and address any potential challenges that might impede their success. The article uses a case study in Jakarta, a rapidly growing megacity that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 34 publications
1
78
0
10
Order By: Relevance
“…The main findings here that perception of hazard-related knowledge does not equate to actual knowledge replicate recent research in Indonesia (Amri et al, 2017) done in an older age cohort in a different country. Here, a very large percentage, nearly 100%, perceived they knew what a forest fire was.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The main findings here that perception of hazard-related knowledge does not equate to actual knowledge replicate recent research in Indonesia (Amri et al, 2017) done in an older age cohort in a different country. Here, a very large percentage, nearly 100%, perceived they knew what a forest fire was.…”
Section: Discussionsupporting
confidence: 73%
“…However, the recent large-scale qualitative study (Towers, 2015) that included 26 focus groups with 87 8-12 year-old children and collateral interviews with 37 parents has demonstrated that children are quite capable of engaging in serious discussions about wildfires. 1 At the same time, small research on wildfire education in school settings has been conducted. The research has demonstrated that schools can play a crucial role in household and local community readiness towards a possible hazardous situation (Ronan et al, 2016;Shaw, Shiwaku, & Takeuchi, 2011).In other words, schools are not only agents for education of children and youth, they can help with "actionable knowledge" transfer to other members of household (Calik, 2013;Ronan et al, 2016) and community (Shaw et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of education for promoting DRR awareness is articulated in the Yokohama Strategy, Hyogo Framework for Action (HFA) 2005 -2015, and the current commitment, the Sendai Framework for Disaster Risk Reduction 2015 -2030 [3]. Since then, there is a wide array of programs internationally to implement disaster preparedness programs in schools [4]. Effective and efficient disaster preparedness education includes accuracy in decision making supported by theoretical knowledge and organizational skills [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, many so-called DRR programs focus on response-preparedness and ignore primary risk reduction [4]. As a result, programs that focus on what to do "in case of disasters" betray a reactive and fatalistic orientation, leading school communities to conclude that they are helpless when it comes to protecting themselves from risk physically [6].…”
Section: Introductionmentioning
confidence: 99%